PERANAN KOMISARIS DAN DIREKSI BANK SYARIAH DALAM PENGELOLAAN DANA ZAKAT DAN ISR (ISLAMIC SOCIAL RESPONSIBILITY) DI INDONESIA - Melia Frastuti; Dimas Pratama Putra; Erfan Effendi (Politeknik Negeri Batam, 2019)
Abstract Almsgiving is one of the pillars supporting the upholding of Islam as the obligation for the adherents to improve horizontal relations between fellow humans and strengthen vertical relations with Allah SWT. The implementation of Islamic Social Responsibility (ISR) of the Islamic Bank gives a positive assessment in sharia agreement, justice and equality, responsibility for work, welfare, guarantee of nature preservation and benevolent assistance that is not profit-oriented. Proper almsgiving management and ISR implementation make Islamic banks trusted by the public in terms of service quality, satisfaction and loyalty of Muzzaki. It reduces bad images, and provides relevant impacts on social welfare and the progress of the era. The data analysis used to test the hypotheses is Multiple Linear Regression analysis. The data is collected by distributing questionnaires to Commissioners and Directors at 14 (fourteen) Islamic Commercial Banks spread throughout Indonesia. The result of this study shows partially prove the role of Islamic bank commissioners in the amsgiving management only, while the importance of the role of directors in Islamic banks in almsgiving management and the implementation of ISR partially. Keywords: Islamic Bank, Commissioners, Directors, Almsgiving and ISR